Acquired Arteriovenous Fistula of the Breast Following Ultrasound Guided Biopsy of Invasive Ductal Carcinoma - Gregg, Adam (Medknow Publications & Media Pvt Ltd, 2013)
Image guided large-core breast biopsies are commonly performed procedures with relatively rare complications. The majority of these complications are minor, though at times more significant vascular injuries can occur with these biopsies as demonstrated by this case. Patient developed a pulsatile vascular breast mass after an ultrasound guided breast biopsy of invasive ductal carcinoma. Sonographic evaluation of this new breast mass demonstrated this mass to represent an arteriovenous fistula (AVF). Though multiple therapies are available for an iatrogenic fistula within the breast, the AVF was surgically excised in this case as it was immediately adjacent to a known cancer.